1998
DOI: 10.2307/1132368
|View full text |Cite
|
Sign up to set email alerts
|

Peer Relationships and Self-Esteem among Children Who Have Been Maltreated

Abstract: A prospective longitudinal design was employed to assess risks associated with maltreatment in a representative community sample of 107 maltreated children and an equal number of nonmaltreated comparison children. Heightened difficulties in peer relationships and self-esteem were associated with greater severity and chronicity of maltreatment. For example, children who experienced chronic maltreatment were less well-liked by peers. Type of maltreatment was also related to specific aspects of children's adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
201
0
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(227 citation statements)
references
References 43 publications
(66 reference statements)
19
201
0
7
Order By: Relevance
“…In line with earlier research [39,40], the adolescents who reported more severe forms of parental violence also reported more severe psychological problems. It is important to note that the exposure to verbal aggression was associated with higher levels of total difficulties, internalizing and externalizing compared with the no violence condition.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with earlier research [39,40], the adolescents who reported more severe forms of parental violence also reported more severe psychological problems. It is important to note that the exposure to verbal aggression was associated with higher levels of total difficulties, internalizing and externalizing compared with the no violence condition.…”
Section: Discussionsupporting
confidence: 89%
“…When a child is exposed to psychological and physical violence, he/she could at the same time be exposed to other forms of maltreatment, such as sexual abuse or physical/emotional neglect. There is evidence that physical and psychological violence (emotional maltreatment) as well as a lack of general supervision tend to co-occur [39]. Likewise, interparental violence (often referred to as domestic violence) and parental violence towards children are, at least to some extent, co-occuring phenomena [45,46].…”
Section: Co-occurring Forms Of Adverse Experiencesmentioning
confidence: 99%
“…These challenges in attachment relationships could potentially lead to the formation of negative models of self, parents, and peers in relationships, and subsequently, deterioration of self-esteem and self-control. In a longitudinal study of peer relationships and self-esteem in maltreated children, results revealed that lack of self-esteem was associated with inadequate and inappropriate parental supervision (Bolger et al 1998). Low self esteem has also been found to be connected to adolescent drug and alcohol abuse (Wild et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Probablemente, más que aludir a la delincuencia en sentido estricto, sería más apropiado ligar este resultado con la emergencia de conductas agresivas y coercitivas (Bolger et al, 1998; Klimes-Dougan y Kistner, 1990;Wolfe et al, 1998), demostrativas de una socialización y funcionamiento social deficientes (Dodge et al, 1994;Okun, Parker, y Levendosky, 1994).…”
Section: Discussionunclassified
“…Tanto los niños de los que se ha abusado como los que han sido abandonados son considerados problemáticos, conflictivos o difíciles, según indicación de sus madres, en el sentido de inestabilidad emocional, deficiente capacidad para la intimidad y mayor exhibición de afecto negativo (Mash, Johnson, y Kovitz, 1983;Parker y Herrera, 1996). Se ha sugerido que la agresividad parece ser un patrón asociado al niño maltratado físicamente, mientras que, en el caso del abandono, es más frecuente que aparezcan dificultades de funcionamiento social y retraimiento (Bolger, Patterson, y Kupersmidt, 1998;Gabel, Swanson, y Shindlecker, 1990;Haskett y Kistner, 1991). Briere y Runtz (1988) encuentran que el maltrato psicológico se relacionó con baja autoestima, el maltrato físico con una predisposición muy alta de agresividad hacia los otros y el abuso sexual con una conducta sexual desadaptada.…”
unclassified